Pharmacologic rationale for treatments of peritoneal surface malignancy from colorectal cancer - Sugarbaker, Paul H (Baishideng Publishing Group Co., Limited, 2010)
The peritoneal surfaces of the abdomen and pelvis are important sites for the dissemination of gastrointestinal and gynecologic malignancy. Transcoelomic dissemination of cancer cells gives rise to carcinomatosis, which, without special treatment, is a fatal manifestation of these diseases. To treat peritoneal carcinomatosis, cytoreductive surgery removes gross disease plus perioperative intraperitoneal and perioperative intravenous chemotherapy eradicates microscopic residual disease and chemical compatibilities. Chemotherapy agents are administered either by the intraperitoneal or intravenous route, based on their pharmacologic properties. A peritoneal-plasma barrier, which retards the clearance of high molecular weight chemotherapy from the peritoneal cavity, results in a large exposure of small cancer nodules on abdominal and pelvic surfaces. Tissue penetration of the intraperitoneal chemotherapy is facilitated by moderate hyperthermia (41-42°C). Targeting of intravenous chemotherapy to the peritoneal surface is facilitated by the intraperitoneal heat. A constant dose of chemotherapy agent and volume of carrier solution, based on body surface area, allows prediction of systemic drug exposure and systemic toxicity. Timing of the hyperthermic chemotherapy as a scheduled part of the surgical procedure to uniformly expose all peritoneal surfaces is crucial to success.